A comparison of two obturation techniques the lateral and vertical condensation method and the Johnson's Twist-off technique - Barretto, Alicia D.
Doctor Ben Johnson introduced a different technique for canal obturation known as the Twist-off technique, wherein a sealer cement, stainless steel files and thermally plasticized gutta-percha were used to obtain a three-dimensional obturation of the root canal system. The technique eliminates the fitting of a master cone thus the need for the tugback is rendered unnecessary. Also the technique does not require the special skills that are needed in other techniques for the apical placement of master cones. This seminar paper was designed to reproduce a smaller scale version of his research. This seminar paper compares the integrity of the apical seal after obturation using the lateral and vertical condensation method and the Johnson's twist-off technique. The result shows that there is no significant difference between the lateral and vertical condensation method as against the Johnson's twist-off technique with regards to the apical seal's integrity.